Regular and Young Investigator Award Abstracts 2022
DOI: 10.1136/jitc-2022-sitc2022.0437
|View full text |Cite
|
Sign up to set email alerts
|

437 Safety and efficacy of immune checkpoint inhibitors (ICI) in patients living with HIV (PLWH) and metastatic non-small cell lung cancer (NSCLC): a matched cohort study from the international CATCH-IT consortium

Abstract: Figure 2 Kaplan-Meier curves for Progression-Free Survival stratified by HIV status Conclusions In this matched cohort study, PLWH and metastatic NSCLC had similar toxicity profiles and clinical outcomes to HIV-counterparts receiving ICI supporting their use in PLWH and their inclusion in clinical trials. Larger

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A few retrospective studies have shown similar ICI efficacy and toxicity in patients with underlying AIDs vs. no AIDs [ 27 , 28 , 29 , 30 ]. In addition, retrospective studies of patients with CVI, including HIV, HBV, and HCV, have shown similar ICI efficacy and safety compared to patients without CVI [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…A few retrospective studies have shown similar ICI efficacy and toxicity in patients with underlying AIDs vs. no AIDs [ 27 , 28 , 29 , 30 ]. In addition, retrospective studies of patients with CVI, including HIV, HBV, and HCV, have shown similar ICI efficacy and safety compared to patients without CVI [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%